Connectivity or complementarity in the dual system : implementation of an exploration study - Bank, Volker [Verfasser] (My University, 2019)
"Tue relationship between learing at school and in-company learning is essential to the understandig of apprenticeship, not only in the frame of the German dual system of vocational education. Around the year 2000 two theoretical approaches have been presented. Among those, the theory of connectivity has instigated a few studies, one of which is presented in the following contribution." (author's abstract; BIBB-Doku)
Keywords: S 3.1 Berufsbildende Schulen; S 3.2 Unternehmen und Behörden; P 2.3 Auszubildende; P 3.2.3 Lehrer; P 3.2.1 Ausbilder; Duales System; Lernort Schule; Lernort Betrieb; Berufsbezug; Literaturanalyse; Kraftfahrzeugmechatroniker; Pflegeberuf; Auszubildender; Berufsschullehrer; Ausbilder